2011
DOI: 10.1111/j.1945-5100.2011.01295.x
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscope‐cathodoluminescence (SEM‐CL) imaging of planar deformation features and tectonic deformation lamellae in quartz

Abstract: Abstract-Planar deformation features (PDFs) in quartz are essential proof for the correct identification of meteorite impact structures and related ejecta layers, but can be confused with tectonic deformation lamellae. The only completely reliable method to demonstrate the shock origin of suspected (sub-) planar microstructures, transmission electron microscope (TEM) observations, is costly and time consuming. We have used a cathodoluminescence (CL) detector attached to a scanning electron microscope (SEM) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 66 publications
4
70
0
Order By: Relevance
“…[24], potential to scan large areas, easy access to complementary SEM imaging modes (e.g. electron channelling contrast image (ECCI) [25] and cathodoluminescence (CL) [26]), and the improvement in angular resolution makes HR-EBSD a powerful technique to study fatigue deformation process in polycrystalline materials. Considerable development of the method has been made such that the analysis generates rather comprehensive deformation information such as intragranular residual stresses (type III) [27], geometrically necessary dislocation (GND) density [28] and total dislocation density [29].…”
Section: *Text Only Click Here To Download Text Only: Manuscript_jun_mentioning
confidence: 99%
“…[24], potential to scan large areas, easy access to complementary SEM imaging modes (e.g. electron channelling contrast image (ECCI) [25] and cathodoluminescence (CL) [26]), and the improvement in angular resolution makes HR-EBSD a powerful technique to study fatigue deformation process in polycrystalline materials. Considerable development of the method has been made such that the analysis generates rather comprehensive deformation information such as intragranular residual stresses (type III) [27], geometrically necessary dislocation (GND) density [28] and total dislocation density [29].…”
Section: *Text Only Click Here To Download Text Only: Manuscript_jun_mentioning
confidence: 99%
“…do not indicate precise specific CL emission wavelength), but indicate in which colour range the main CL emission of a feature in the sample is. See Hamers and Drury (2011) for a more detailed discussion of SEM-CL imaging.…”
Section: Methodsmentioning
confidence: 99%
“…A one-to-one correlation of SEM-CL and TEM showed that the non-luminescent shock features were amorphous PDFs, whereas the red CL type was healed PDFs or shock induced Brazil twins (Hamers et al 2016). Tectonic deformation lamellae show red to blue CL (Hamers and Drury 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Ferriere et al, 2009;French and Koeberl, 2010;Hamers and Drury, 2011;Glikson and Uysal, 2013). Duane and Reimold (1990) and Ordovician pelagic to shelf clastic sediments (Gatehouse et al, 1995;Gravestock and Gatehouse, 1995;Radke, 2009;Roberts et al, 1990;Sun, 1997Sun, , 1998Sun, , 1999Sun et al, 1994).…”
Section: Warburton West Manuscript Minor Changes Applied 12-12-2014mentioning
confidence: 99%